HUBUNGAN KECERDASAN SPIRITUAL DENGAN STRES PASIEN DIABETES MELLITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS II DENPASAR BARAT - Minfiatin Malikatin; Meril Valentine Manangkot; Luh Mira Puspita (Coping: Community of Publishing in Nursing, 2021)
ABSTRACT Diabetes Mellitus is a metabolic disorder that occurs due to the pancreas not being able to produce sufficient insulin effectively. The increasing number of DMT2 patients can be caused by several factors, namely genetic factors, obesity, aging, smoking, and stress. Stress can be influenced by several factors, namely material, physical, psychological, social, and spiritual (such as spiritual intelligence). Spiritual intelligence is a dimension of a person to gain strength when facing physical illness and psychological problems. This study aimed to identify the relationship between spiritual intelligence with the stress of Diabetes Mellitus Type 2 patients in the working area of Public Health Center (Puskesmas) II West Denpasar. This study used a descriptive correlative design with a cross-sectional approach. A total of 44 respondents were involved and selected by consecutive sampling techniques in this study. The instruments used were the Spiritual Intelligence Self-Report Inventory (SISRI) and the Depression Anxiety Stress Scales (DASS) questionnaires. The Spearman Rank test results obtained p=0,484 (p>0,05) value, which means there was no significant relationship between spiritual intelligence with the stress of DMT2 patients in the working area of Public Health Center (Puskesmas) II West Denpasar. This study is expected to use a larger number of samples, thus the data obtained will be more accurate and the spiritual intelligence of Diabetes Mellitus patients need to be more considered by a nurse when providing nursing care to Diabetes Mellitus patients. Therefore, it can support other aspects that contribute to the patient's self-care abilities.Keywords: Spiritual Intelligence, DMT2 Patient, Stress